Brain activity induced by implicit processing of others' pain and pleasure. Issue 11 (18th August 2017) - Chiesa, Patrizia Andrea; Liuzza, Marco Tullio; Macaluso, Emiliano; Aglioti, Salvatore Maria
Abstract: Studies indicate that both explicit and implicit processing of affectively charged stimuli may be reflected in specific behavioural markers and physiological signatures. Here, we investigated whether the pleasantness ratings of a neutral target were affected by the subliminal perception of a painful (a slap) or pleasant (a caress) touch delivered to others. In particular, we combined the continuous flash suppression technique with the affective misattribution procedure to explore subliminal processing of observed pain and pleasure in others. Results show that participants rated the neutral target as more or less likeable depending on whether they were subliminally primed with the pleasant or painful facial expression, respectively. The fMRI activity associated with painful and pleasant subliminal priming was mainly present in the anterior prefrontal cortex and the primary sensorimotor cortex, respectively. Thus, our study provides behavioural and neuro‐physiological evidence that: (i) emotional reactivity toward positive or negative states of others can occur at an entirely subliminal level; (ii) specific neural substrates underpin reactivity to positive‐ and negative‐valence of social emotions. Hum Brain Mapp 38:5562–5576, 2017 . ©2017 Wiley Periodicals, Inc.